Silibinin Induced Autophagic and Apoptotic Cell Death in HT1080 Cells Through a Reactive Oxygen Species Pathway - Wenjun Duan; Xiaoying Jin; Qisheng Li; Shin-ichi Tashiro; Satoshi Onodera; Takashi Ikejima (Elsevier, 2010)
Hepatoprotectant silibinin has anticancer and chemo-preventive effects. In this study, silibinin showed significant inhibitory effect on human fibroblast HT 1080 cell growth cultured in media containing 10% fetal bovine serum or in serum free media, and in the latter case, silibinin exerted a more significant effect. Silibinin induced autophagy at 12 h, confirmed by monodansyl-cadervarine (MDC) staining, up-regulation of Beclin 1 (initiation factor for autophagosome formation), and conversion of LC3 I to LC3 II (autophagosome marker). It also induced apoptosis at 24 h, proved by observation of apoptotic body and activation of caspase-3. 3-Methyladenine (3-MA) inhibited silibinin-induced autophagy and promoted cell survival, suggesting that autophagy enhanced silibinin-induced apoptosis in HT1080 cells. Silibinin generated reactive oxygen species (ROS) in HT1080 cells, and the ROS scavenger N-acetylcysteine (NAC) reversed the cytotoxicity of silibinin, resulting in cell survival by inhibition of autophagic and apoptotic pathways. Application of specific antioxidants demonstrated that H2O2 was a major factor in silibinin-induced ROS since the H2O2 scavenger catalase reduced both autophagy and cell death. O2•− also contributed to silibinin-induced cell death. Keywords:: silibinin, H1080 cell, autophagy, apoptosis, reactive oxygen species